Sistem Pendukung Keputusan Mahasiswa Berprestasi Menggunakan Metode Kombinasi Analytical Hierarchy Process (AHP) dan Simple Additive Weigting (SAW) - Lukas Arief Prasetyo (Universitas Indraprasta PGRI Jakarta, 2018)
The selection of outstanding students at Secretary Academy of Budi Luhur has long been conducted from the collection of scores involving lecturers and staff. The collected data are then given to the Head of Study Program for the selection. The method is considered less effective because it uses manual calculation and shows no objectivity in the student assessment in which the scores given by lecturers and staff are only based on their estimation and closeness to students. The Head of the Study Program takes a long time to make a decision. Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) are methods that can be used to select outstanding students based on the criteria set in Dikti guidelines 2016. The Analytical Hierarchy Process (AHP) is used in weighting process, while the Simple Additive Weighting (SAW) is used in ranking process. It is expected that the weighting and ranking processes can create an effective and objective decision support system application.